2015
DOI: 10.3329/fmcj.v9i2.25678
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Urban Adolescent Students of Some Selected Schools

Abstract: :To determine the factors related with depression among adolescent students, 165 male adolescent students aged 15 to 19 years from 2 urban schools and colleges were interviewed with semi-structured questionnaire during January to June 2012.The socio demographic details, smoking and depression histories were recorded. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure the presence of depression. Smoking behavior was measured by a number of questions. Almost 49% respondents were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
5
5
Order By: Relevance
“…Compared to previous studies in Bangladesh among adolescents, the prevalence of depression in the present study was higher (26.5% vs. 25%) than a previous study conducted in 2013 among 898 adolescents aged 13–16 years in Dhaka City [ 28 ]. The prevalence of depression in the present study was lower (26.5% vs. 36.6%) than a study conducted in 2018 among 311 adolescents aged 13–17 years in Dhaka (urban and semi-urban areas) [ 11 ] and also lower (26.5% vs. 49%) compared to a previous study conducted in 2012 among 165 adolescents aged 15–19 years selected from two urban schools in Bangladesh [ 29 ]. In the present study, one-fifth of respondents (18.1%) experienced moderate to severe anxiety.…”
Section: Discussioncontrasting
confidence: 85%
“…Compared to previous studies in Bangladesh among adolescents, the prevalence of depression in the present study was higher (26.5% vs. 25%) than a previous study conducted in 2013 among 898 adolescents aged 13–16 years in Dhaka City [ 28 ]. The prevalence of depression in the present study was lower (26.5% vs. 36.6%) than a study conducted in 2018 among 311 adolescents aged 13–17 years in Dhaka (urban and semi-urban areas) [ 11 ] and also lower (26.5% vs. 49%) compared to a previous study conducted in 2012 among 165 adolescents aged 15–19 years selected from two urban schools in Bangladesh [ 29 ]. In the present study, one-fifth of respondents (18.1%) experienced moderate to severe anxiety.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of depressive symptoms found in the present study is however much lower than the 49% reported in another study conducted in 2012, and using the same questionnaire (CESD) with 165 urban adolescents selected from two urban schools in Bangladesh (Billah and Khan 2014). That other study was with older adolescents aged 15-19 years (as opposed to 13-16 years in the present study), and the present study demonstrated much higher odds of depression among older than younger adolescents.…”
Section: Discussioncontrasting
confidence: 78%
“…Four in five adolescents report high (≥2 hours/day) recreational screen time with a median of 4.0 hours/day of screen time (Khan & Burton, 2016), and one in three adolescents do not meet the World Health Organization (WHO) recommendations of 60 mins/day of MVPA . One recent study found that one in two adolescents in urban Bangladesh has depressive symptoms; this was defined as a score of ≥ 22 using the 20-item Center for Epidemiologic Studies Depression Scale (CESD20) (Billah & Khan, 2014). Understanding the inter-relationships among screen time, physical inactivity, and mental health therefore has significant public health implications in this developing country.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…regardless of screen time) . Other studies using different measures of depressive symptoms, adolescents of varying age ranges, and including adolescents from regional areas have reported prevalence of depressive symptoms ranging from 14% (Nasreen et al, 2016) to 49% (Billah & Khan, 2014), and from 36% (Rodrigo et al, 2010) to 59% (Verma et al, 2014) in other Asian countries. Just under a third of those with high screen time did not meet physical activity recommendations.…”
mentioning
confidence: 99%